2019
DOI: 10.3390/nu11051036
|View full text |Cite
|
Sign up to set email alerts
|

3-(4-Hydroxy-3-methoxyphenyl)propionic Acid Produced from 4-Hydroxy-3-methoxycinnamic Acid by Gut Microbiota Improves Host Metabolic Condition in Diet-Induced Obese Mice

Abstract: 4-Hydroxy-3-methoxycinnamic acid (HMCA), a hydroxycinnamic acid derivative, is abundant in fruits and vegetables, including oranges, carrots, rice bran, and coffee beans. Several beneficial effects of HMCA have been reported, including improvement of metabolic abnormalities in animal models and human studies. However, its mitigating effects on high-fat diet (HFD)-induced obesity, and the mechanism underlying these effects, remain to be elucidated. In this study, we demonstrated that dietary HMCA was efficaciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…For instance, 10-hydroxy- cis -12-octadecenoic acid is an initial linoleic acid-related gut-microbial metabolite, which attenuates HFD-induced obesity in mice by improving the metabolic profile via free fatty acid receptors and by enhancing intestinal barrier function . 3-(4-Hydroxy-3-methoxyphenyl) propionic acid, produced by gut microbiota, is a metabolically beneficial metabolite that regulates hepatic lipid metabolism and insulin sensitivity . There is a bidirectional regulation between gut microbiota and host metabolism.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…For instance, 10-hydroxy- cis -12-octadecenoic acid is an initial linoleic acid-related gut-microbial metabolite, which attenuates HFD-induced obesity in mice by improving the metabolic profile via free fatty acid receptors and by enhancing intestinal barrier function . 3-(4-Hydroxy-3-methoxyphenyl) propionic acid, produced by gut microbiota, is a metabolically beneficial metabolite that regulates hepatic lipid metabolism and insulin sensitivity . There is a bidirectional regulation between gut microbiota and host metabolism.…”
Section: Introductionmentioning
confidence: 59%
“…18 3-(4-Hydroxy-3-methoxyphenyl) propionic acid, produced by gut microbiota, is a metabolically beneficial metabolite that regulates hepatic lipid metabolism and insulin sensitivity. 19 There is a bidirectional regulation between gut microbiota and host metabolism. Tryptophan and its endogenous host metabolites have modulatory effects on gut microbial composition and microbial functions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Third, the Clostridium cluster IX levels were also significantly lower (p=0.045) in the PH group than in the non-PH-G. This cluster is said to have many strains that produce propionic acid; however, for most strains, the effect on the host and function in the human intestines remains largely unknown (25,26). In light of our results, these topics represent further questions that should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…p -hydroxybenzoic acid is mainly obtained from the oxidation of 2-(4-hydroxyphenyl) ethanol in the process of acetic acid fermentation [ 41 ]. It was found that 3-(4-hydroxy-3-methoxyphenyl) propionic acid has anti-oxidative activity, which was related to anti-inflammatory effects and regulation of lipid metabolism [ 42 ]. Chlorogenic acid, as a polyphenol monomer, was as abundant in vinegar as other fruit vinegar [ 10 ].…”
Section: Resultsmentioning
confidence: 99%